Arts-based assessment in educational settings - Jiří Kantor; Xianmei Lei (International Journal of Evaluation and Research in Education (IJERE), 2020)
Arts-based assessment is an objective measure that incorporates artistic experience or artistic materials into the assessment process and enables to get unique contributions about pupils. The current survey focused on arts-based assessment in the Czech Republic to explore the following issues: how did arts therapists assess suitability of therapy for pupils; which areas of therapeutic process were evaluated and what made the process of arts-based assessments specific in educational institutions. A mixed methods study used a statistical analysis of a survey with “The Practice in Arts Therapies questionnaire” (n = 142 arts therapists) and an inductive analysis of qualitative interviews (n = 10 arts therapists). Results revealed that arts-based assessments were more likely to be characterized by qualitative nonstandardized assessments based on observation, analysis of artistic products/artistic process and reflexive techniques and are related to prevalent humanistic orientation. Educational environment influenced the assessments mainly in the content and organization of the process. On this basis, there is a need to support the usage of standardized arts-based assessments and to develop standards for the implementation of arts-based assessment suitable for educational institutions. More advanced training in this area should be included into professional courses and further education of arts therapists.